2002
DOI: 10.1002/oti.162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes research from the occupational therapist's perspective

Abstract: With increasing costs and scarcity of resources, occupational therapists need to embrace outcomes research to demonstrate the effectiveness of its clinical interventions. To explore clinicians' perspectives on clinical outcomes research a qualitative study was undertaken involving three in-depth group interviews with 15 occupational therapists from the South Western Sydney Area Health Service. Five broad themes permeated participants' perception: (a) defining the process, (b) factors that impact on participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…This appears to reflect previous findings that some occupational therapists have difficulty measuring clinical outcomes (Bowman & Llewellyn, 2002). With the UK government promising that care in the NHS will focus on continuously improving those things that really matter to patients, particularly the outcome of their healthcare (Department of Health, 2010), it is important for occupational therapists to increase their use of outcome measures.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This appears to reflect previous findings that some occupational therapists have difficulty measuring clinical outcomes (Bowman & Llewellyn, 2002). With the UK government promising that care in the NHS will focus on continuously improving those things that really matter to patients, particularly the outcome of their healthcare (Department of Health, 2010), it is important for occupational therapists to increase their use of outcome measures.…”
Section: Discussionsupporting
confidence: 79%
“…It has been suggested that few occupational therapists measure clinical outcomes because they struggle to articulate clearly their goals and interventions (Bowman and Llewellyn, 2002). The future of health services in the UK will be one where providers of services will be paid according to the quality of performance which reflects outcomes and not simply activity (Department of Health, 2010).…”
Section: Word Count: 3985 Evaluating Outcomes Of Therapies Offered Bymentioning
confidence: 99%
“…A complex interplay of personal characteristics, professional culture, and context influences whether occupational therapists take up the challenge of thoroughly examining their clinical interventions (16). Development into evidence-based practice will involve high levels of personal change as it requires reflection, planning, and action in a local context over long periods of time (17) Despite a growing awareness that implementation of evidence in practice is a complex, multifaceted process, a lack of knowledge remains as to what methods and approaches are effective, with whom, and in what contexts (13).…”
Section: Implementing Evidence-based Practice In Occupational Therapymentioning
confidence: 99%
“…The COPM has been used extensively in occupational therapy research (Bowman & Llewellyn, 2002;Law et al, 1998). It uses a semistructured interview format with standardized methods for administration and scoring, and it has established reliability and validity (Bosch, 1995;Chan & Lee, 1997;Cup, Scholte op Reimer, Thijssen, & van Kuyk-Minis, 2003).…”
Section: Instrumentsmentioning
confidence: 99%